2016
DOI: 10.1039/c6ra25016e
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the effect of surface functional groups on catalytic performance for hydrogen generation from sodium borohydride

Abstract: Sodium borohydride hydrolysis to generate hydrogen has great potential for mobile and portable applications, and designing efficient catalysts for this reaction is indispensable. In this work, the effect of surface functional groups on hydrogen generation rate (HGR) is investigated using two polystyrene resin supported Pt catalysts. The first type of resin (resin-NH) contains -N(CH 3 ) 3 OH and abundant -OH groups, while the other one (resin-SH) contains -SO 3 H and less -OH. After excluding the influences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The catalytic performance of this modified ZIF‐8 material was superior to the other supports including GO, AC, and mesoporous SiO 2 (SBA‐15) (Table 2). Further kinetic isotope effect studies revealed a high value of 4.95, suggesting that the cleavage of the water's OH bond was the rate‐determining step in this process [41b,51] . Given the hydridic nature of the BH bond in AB, a hydrogen bond between H 2 O and AB molecule at the catalyst surface can be formed and this would facilitate the release of hydrogen from AB through the oxidative addition of OH on Pt–Ni alloy structure (Figure 7b).…”
Section: Catalyzed Hydrolysis Of Hydrides: Means To Generate Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic performance of this modified ZIF‐8 material was superior to the other supports including GO, AC, and mesoporous SiO 2 (SBA‐15) (Table 2). Further kinetic isotope effect studies revealed a high value of 4.95, suggesting that the cleavage of the water's OH bond was the rate‐determining step in this process [41b,51] . Given the hydridic nature of the BH bond in AB, a hydrogen bond between H 2 O and AB molecule at the catalyst surface can be formed and this would facilitate the release of hydrogen from AB through the oxidative addition of OH on Pt–Ni alloy structure (Figure 7b).…”
Section: Catalyzed Hydrolysis Of Hydrides: Means To Generate Hydrogenmentioning
confidence: 99%
“…This makes Pt electron rich and eases the electron transfer process (Figure 4) to the defective support in line with the recent studies. [ 41 ] Hence, the defective surface triggers an electron transfer process from the metal site to the support and promotes AB hydrolysis to generate H 2 . On the other hand, electron‐rich oxygen groups, where the electron‐deficient metal is anchored, are believed to reverse this process (Figure 4).…”
Section: Catalyzed Hydrolysis Of Hydrides: Means To Generate Hydrogenmentioning
confidence: 99%
“…Modification of catalyst support surface is one possible solution to increase catalysts' activity and stability. The presence of functional groups on the support surface has great influence on the electronic state of active metal and metal dispersion [21]. The aminopropyl groups provide a unique possibility for further surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of catalyst support surface is possible solution to increase catalysts activity and stability. Presence of functional groups on support surface has great influence on electronic state of active metal and metal dispersion [21]. The aminopropyl groups presence a unique possibility for further surface modification.…”
Section: Introductionmentioning
confidence: 99%